Stolen Asset Recovery : A Good Practices Guide for Non-conviction Based Asset Forfeiture - Greenberg, Theodore S. (World Bank, 2012)
The guide is organized into three major parts: Part A first provides an overview of the problem of stolen assets and the problem of recovering the assets once they are transferred abroad. Second, it describes how the international community has taken steps to respond to the problem through United Nations Convention against Corruption (UNCAC) and the Stolen Asset Recovery (StAR) Initiative. UNCAC introduced a new framework to facilitate the tracing, freezing, seizing, forfeiture, and return of assets stolen through corrupt practices and hidden in foreign jurisdictions. The StAR Initiative developed an action plan to support the domestication and implementation of asset recovery provisions under UNCAC, to facilitate countries' efforts to recover stolen assets that have been hidden in foreign jurisdictions, and ultimately, to help deter such flows and eliminate safe havens for hiding corruption proceeds. Third and finally, Part A introduces non-conviction based (NCB) asset forfeiture as one of the critical tools to combat corruption, describing the situations when it is useful, how it differs from criminal forfeiture, its usefulness in civil and common law jurisdictions, and the support it has gained internationally. Part B contains the 36 key concepts. The concepts have been grouped together by topic area, including prime imperatives, definitions of assets and offenses subject to NCB asset forfeiture, measures for investigation and preservation of assets, procedural and evidentiary concepts, determining parties and ensuring proper notice, judgment proceedings, organizational considerations and asset management, and international cooperation and asset recovery. The concepts are illustrated through examples from cases and excerpts from different jurisdictions' NCB asset forfeiture legislation. Part C contains a number of special contributions written by individual practitioners. The contributions focus on the general practice of NCB asset forfeiture and international cooperation in specific jurisdictions, namely Colombia, Guernsey, Ireland, Kuwait, Switzerland, Thailand, and the United Kingdom. In addition, some contributions illustrate a selection of NCB asset forfeiture practices, such as asset management, delegating certain roles to the executive branch, and pursuing forfeiture based on illicit enrichment.